The efficiency of laser treatment of familial exudative vitreoretinopathy in children - E. V. Denisova; E. A. Geras’kina; L. A. Katargina (Российский офтальмологический журнал)
Familial exudative vitreoretinopathy (FEVR) is a hereditary disease characterized by abnormal angiogenesis and avascular zones (AZ) on the retinal periphery. The leading method of treatment of its early stages (1–3) is laser coagulation (LC) of AZ and pathological retinal vessels.Purpose. To study the efficiency of retinal laser coagulation in children with various stages of FEVR.Material and methods. 65 children with FEVR (82 eyes) were observed after retinal LC for 6 months to 10 years (on average, 3 years). The efficiency of laser treatment was evaluated after 2–3 months. We regarded the result as stabilization if no progression of the disease could be observed over the entire follow-up period (at least 12 months), either with or without an additional LC.Results. The efficiency of a single LC in children with FEVR in stage 1 was 100 %, in stage 2, 50 to 56 %, in stage 3, 10 to 50 %, in stage 4, 20 to 33 %. The proportion of cases with long-term (over 12 months) stabilization after additional LC sessions was diminishing according to the initial severity of clinical manifestations: from 75–100 % in stages 1–2 to 41–60 % in stage 3 and to 17–20 % in stage 4.Conclusion. LC efficiency of AZ and pathological retinal vessels in children with FEVR is inversely proportional to the stage of the disease. In more than half of the cases, repeated sessions of LC are required to achieve stabilization. The persistence of vascular activity after LC or the appearance of new vascular malformations are prognostic signs of further FEVR progression. The results obtained indicate the need for an early detection of the disease and an LC procedure to prevent the development of extensive retinal detachment, as well as regular dynamic observation of the patients and further study of the pathogenetic mechanisms of FEVR progression.